Unequal depth beam-column joints with H-shaped damper: Parametric study and design method. (1st February 2022) - Mou, Ben; Zhou, Yang; Wang, Fangying; Liu, Jiming
Highlights: Three types of H-shaped dampers were designed. H-shaped dampers could improve the shear strength and deformation of the panel zone. Web perforated forms influenced the performance of the H-shaped damper. Abstract: This paper proposes new types of unequal depth beam-column (UDBC) steel joints with H-shaped damper. The seismic energy was dissipated through the elastoplastic deformation of H-shaped steel dampers. Based on the experimental results, detailed three-dimensional finite element models were built to identify the response of UDBC joints under cyclic loadings. Three types of H-shaped dampers (vertical damper, elliptical damper, and diamond damper) were designed. Then, the shear capacity of the unequal-depth panel zones and the energy dissipation capacity of H-shaped damper were studied by the parametric analysis. The result showed that H-shaped dampers could improve the shear strength and deformation of the panel zone significantly. Moreover, web perforated forms influenced the performance of the H-shaped damper. With the increasing of limb width or decreasing of limb height, the shear strength and shear deformation of the panel zone increased, and cumulative energy dissipation of dampers decreased.